Prediabetes is Characterized by Higher FGF23 Levels and Higher Prevalence of Vitamin D Deficiency Compared to Normal Glucose Tolerance Subjects - Gateva, Antoaneta; Assyov, Yavor; Tsakova, Adelina; Kamenov, Zdravko (Hormone and Metabolic Research, 2019)
In the last years there is an increasing interest towards the bone as an endocrine organ and the role of bone and calcium-phosphate metabolism markers in a range of metabolic disturbances. The aim of the present study is to assess the changes of calcium phosphate metabolism markers in patients with prediabetes compared to normogycemic controls and their link to glucose disturbances and cardiovascular risk factors. In this study, 80 patients with mean age 50.4±10.6 years were included, divided into 2 age- and BMI-matched groups – group 1 with obesity without glycemic disturbances (n=41) and group 2 with obesity and prediabetes (n=39). Oral glucose tolerance test (OGTT) with measurement of immunoreactive insulin was performed in all participants and levels of PTH, 25(OH)D, FGF23, and Klotho were measured. We found significantly higher levels of FGF23 in patients with prediabetes compared to normal glucose tolerance subjects (10.4±10.7 vs. 5.8±7.3 pg/ml; p=0.03). FGF23 showed a weak positive correlation to fasting blood glucose (r=0.224; p=0.048) but not to blood glucose on the first and second hour of oral glucose tolerance test or insulin levels. There was extremely high prevalence of vitamin D deficiency in both groups. Lower levels of 25(OH)D were observed in prediabetes group, although without statistical significance (p=0.57). Patients with prediabetes have higher FGF23 levels and higher prevalence of vitamin D deficiency compared to normal glucose tolerance subjects. Elevated FGF23 levels seem to be correlated more to elevated fasting blood glucose levels than to insulin resistance state of the patients.
Keywords: prediabetes; FGF23; klotho; vitamin D; insulin resistance